2013
DOI: 10.1212/wnl.0b013e31829e6fd2
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of nigrosome 1 and its loss in PD

Abstract: Objective: This study assessed whether high-resolution 7 T MRI allowed direct in vivo visualization of nigrosomes, substructures of the substantia nigra pars compacta (SNpc) undergoing the greatest and earliest dopaminergic cell loss in Parkinson disease (PD), and whether any disease-specific changes could be detected in patients with PD.Methods: Postmortem (PM) midbrains, 2 from healthy controls (HCs) and 1 from a patient with PD, were scanned with high-resolution T2*-weighted MRI scans, sectioned, and staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
258
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(285 citation statements)
references
References 29 publications
20
258
1
6
Order By: Relevance
“…Absence of this MRI feature resulted in 85.7% sensitivity and 100% specificity to detect PD. We suggest that this MRI feature reported at 7T MRI using T2*-weighted sequences 1 can also be detected at 3T using SWI sequences and that absence of this MRI feature might have potential for diagnosing PD.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Absence of this MRI feature resulted in 85.7% sensitivity and 100% specificity to detect PD. We suggest that this MRI feature reported at 7T MRI using T2*-weighted sequences 1 can also be detected at 3T using SWI sequences and that absence of this MRI feature might have potential for diagnosing PD.…”
mentioning
confidence: 73%
“…Editors' Note: The inability to visualize nigrosome 1 on a 7T brain MRI is suggestive of Parkinson disease, as described by Blazejewska 1 identified a hyperintense ovoid area within the dorsolateral border of the otherwise hypointense pars compacta of the substantia nigra (SNc) in healthy controls (HC) and the absence of this MRI feature 2 in patients with Parkinson disease (PD) using T2*-weighted 7T MRI. Moreover, the postmortem 7T MRI with histopathologic correlations suggested that this MRI feature corresponded to nigrosome 1.…”
mentioning
confidence: 99%
“…By using 7T [3][4][5][6] and 3T MR imaging, 7,8 recent studies demonstrated that nigrosome 1 can serve as a surrogate biomarker for IPD. Schwarz et al 7 obtained high-resolution 3D gradient recalled-echo imaging (voxel size, 0.55 ϫ 0.55 ϫ 0.7 mm) in an imaging plane parallel to the splenium-genu line at 3T.…”
Section: Discussionmentioning
confidence: 99%
“…Although we enrolled only patients with clinically well-established IPD, the specificity of our study was lower (84.6%) than that in the studies with 7T MR imaging (87.5%-96.2%). 5,6,9 Thus, a more specific imaging biomarker that could give confirmation to patients with clinical suspicion of parkinsonism is still needed. 21,22 On the basis of our results of a relatively lower specificity than that of previous studies, nigrosome 1 detection at 3T MR imaging should be further improved to serve as a confirmatory test of IPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation